Wujud Inferioritas dan Superioritas Tokoh Raja dalam Film Cinta Pertama, Kedua, & Ketiga karya Gina S.Noer (Analisis Psikologi Individual Alfred Adler) - Zulfah, Amarel Aulia; Martini, Laura Andri Retno; Purnomo, Mulyo Hadi (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2023)
This study aims to describe the forms of inferiority and superiority of the Raja character in The First, Second, & Third Love films, which will be released in 2022. This study uses the theory of film narrative structure, literary psychology, and Alfred Adler's individual psychology. This research includes library research using descriptive qualitative methods by utilizing interpretation methods by presenting them in the form of descriptions. The data were obtained by watching and understanding the storyline of the First, Second, & Third Love films, taking several scenes of the Raja character with other characters, recording data related to the form of the inferiority and superiority of the Raja character, and grouping the data results with an adapted format. The technique of presenting the results of data analysis is presented in the form of a description. The results of this study indicate that: First, the form of the inferiority of the Raja character includes feelings of doubt, weakness, helplessness, worry, shame, and fear. Second, the form of the superiority of the Raja figure is finding happiness, a sense of responsibility arises, a feeling of sympathy arises, and a feeling of courage arises.